Pembuatan Hand And Body Lotion Dari Ekstrak Rimpang Kunyit Dengan Menggunakan Metode Maserasi - Ariani, Nita; Nahar, Nahar; Diana, Selvie (Jurnal Riset, Inovasi, Teknologi & Terapan, 2022)
Turmeric (Curcuma longa) is one of the most useful plants that can grow and develop throughout Indonesia. Turmeric is known to have high curcumin content so it has several pharmacological effects such as antioxidants. This study aims to produce a turmeric extract lotion preparation and to test the physical quality according to the Indonesian National Standard (SNI-16-4399- 1996). This research method is experimental which consists of making simplicia and extraction using maceration with 96% ethanol as solvent. The formulation used turmeric extract with a volume of 1 ml, 3 ml and 6 ml and the addition of carrageenan concentrations with a mass of 1gr, 1.5gr, 2gr, 2.5gr and 3gr. Evaluation of the physical quality characteristics of lotion preparations included organoleptic observation, homogeneity testing, absorbency test and pH test. The results showed that the three extract concentration formulas produced a homogeneous lotion, thick, smooth texture, odorless, light yellow, light orange and yellow. Hand and body lotion with the use of 3gr carrageenan added with 6 ml turmeric extract resulted in a homogeneous appearance; pH 7.0; viscosity 23600 cPs. The addition of turmeric extract produces hand and body lotion that meets the standards of SNI 4399-1996.